Targeting NK Cell Checkpoint Receptors or Molecules for Cancer Immunotherapy - Zhang, Cai; Liu, Yuxia (Frontiers in Immunology, 2020)
Checkpoint blockade therapy, for example using antibodies against CTLA-4 and PD-1/PD-L1, relieves T cells from the suppression by inhibitory checkpoints in the tumor microenvironment; thereby achieving good outcomes in the treatment of different cancer types. Like T cells, natural killer (NK) cell inhibitory receptors function as checkpoints for NK cell activation. Upon interaction with their cognate ligands on infected cells, tumor cells, dendritic cells and regulatory T cells, signals from these receptors severely affect NK cells' activation and effector functions, resulting in NK cell exhaustion. Checkpoint inhibition with antagonistic antibodies (Abs) can rescue NK cell exhaustion and arouse their robust anti-tumor capacity. Most notably, the response to anti-PD-1 therapy can be enhanced by the increased frequency and activation of NK cells, thereby increasing the overall survival of patients with multiple types of cancer. In addition, rescue of NK cell activity could enhance adaptive T cells' anti-tumor activity. Some antagonistic Abs (e.g., anti-TIGIT and anti-NKG2A monoclonal Abs) have extraordinary potential in cancer therapy, as evidenced by their induction of potent anti-tumor immunity through recovering both NK and T cell function. In this review, we summarize the dysfunction of NK cells in the tumor microenvironment and the key NK cell checkpoint receptors or molecules that control NK cell function. We particularly focus on recent advances in the most promising strategies through blockade of NK cell checkpoints or their combination with other approaches to more effectively reject tumors.